The Moderating Role of Big Five Personality in the Relationship between Digital Financial Literacy, Fintech Skills, and Financial Well-Being among MSMEs in Kupang City - M. E. Perseveranda; Marianus Antonius Deo Datus Banase; Maria Imakulata Pongge (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
This study examines the relationship between digital financial literacy, fintech skills, Big Five Personality, and financial well-being among micro-enterprise owners in Kupang City, Indonesia. The study applies a quantitative explanatory design using survey data collected from 283 active micro-enterprise owners. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4, including measurement model evaluation, structural model evaluation, and bootstrapping with 5,000 subsamples. The results show that digital financial literacy has a positive and significant effect on fintech skills, but it does not directly affect financial well-being. Fintech skills have a positive and significant effect on financial well-being and fully mediate the relationship between digital financial literacy and financial well-being. Big Five Personality has a direct effect on financial well-being, but it does not significantly affect fintech skills and does not moderate the relationship between digital financial literacy and fintech skills or financial well-being. These findings indicate that digital financial literacy contributes to financial well-being when it is translated into practical fintech skills. The study suggests that financial education for micro-enterprises should move beyond conceptual literacy and focus on hands-on fintech training related to digital payments, cash-flow recording, and business financial management